2015
DOI: 10.1016/j.envint.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate: A review of human exposure, biomonitoring and the environmental forensics utility of its chirality and isomer distribution

Abstract: Perfluorooctane sulfonate (PFOS) found extensive use for over 60 years up until its restriction in the early 2000s, culminating in its listing under the Stockholm Convention on Persistent Organic Pollutants (POPs) in 2009. Efforts to minimise human body burdens are hindered by uncertainty over their precise origins. While diet appears the principal source for the majority of western populations (with other pathways like dust ingestion, drinking water and inhalation also important contributors); the role played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 130 publications
(162 reference statements)
3
58
1
1
Order By: Relevance
“…An in vitro study using human microsomes showed that branched chain perfluorooctane sulfonamides (PFOSAs, PFOS precursor) to be preferentially metabolized to PFOS relative to linear PFOSAs ). Studies show that exposure to PFOS precursors in becoming more important compared to direct exposure, suggesting more precautions should be taken in the further PFASs study (Miralles-Marco and Harrad 2015). A relative higher proportion of n-PFOS in maternal serum sample from Canada (80% n-PFOS, Benskin et al 2007), Norway (78% n-PFOS, Haug et al 2011), and Vietnam (83% n-PFOS, Rylander et al 2009b) may suggest that n-PFOS appears to undergo less facile cross-placental transport.…”
Section: Isomeric Profile Of Pfos In Cord Serummentioning
confidence: 94%
See 1 more Smart Citation
“…An in vitro study using human microsomes showed that branched chain perfluorooctane sulfonamides (PFOSAs, PFOS precursor) to be preferentially metabolized to PFOS relative to linear PFOSAs ). Studies show that exposure to PFOS precursors in becoming more important compared to direct exposure, suggesting more precautions should be taken in the further PFASs study (Miralles-Marco and Harrad 2015). A relative higher proportion of n-PFOS in maternal serum sample from Canada (80% n-PFOS, Benskin et al 2007), Norway (78% n-PFOS, Haug et al 2011), and Vietnam (83% n-PFOS, Rylander et al 2009b) may suggest that n-PFOS appears to undergo less facile cross-placental transport.…”
Section: Isomeric Profile Of Pfos In Cord Serummentioning
confidence: 94%
“…Results showed that in utero PFOS and PFOA exposure was associated with decreased measure of birth weight in most studies, but only some results were significant (Bach et al 2015). The chirality of PFAS isomers may have important environmental significance because different enantiomers can interact with various biological large molecules, leading to different toxicological responses (Miralles-Marco and Harrad 2015). Studies showed that branched PFASs were eliminated faster than the linear PFASs in rats ), fish (De Silva et al 2009b), and occupational workers (Gao et al 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Seafood and freshwater fish have been identified as important contributors to dietary exposure to PFOS and long-chain PFCAs Berger et al, 2009;Fromme et al, 2009;Haug et al, 2010;Rylander et al, 2010), whereas a varied picture has been seen for other PFASs (Herzke et al, 2013;Vestergren et al, 2012). In addition, several biological factors play a role in the burden of PFASs in the body, including age, gender, reproductive factors, and compound specific toxicokinetics Denys et al, 2014;Harada and Koizumi, 2009;Haug et al, 2010;Lorber et al, 2015;Miralles-Marco and Harrad, 2015;Nost et al, 2014). In this context, toxicokinetic models are useful for the quantitative interpretation of biomonitoring data and exposure prediction (Hölzer et al, 2011;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Human exposure to PFASs can occur via contact with consumer products, ingestion of house dust, transfer from food packaging, or via drinking water (Domingo, 2012;Fromme et al, 2009;Kotthoff et al, 2015;Miralles-Marco and Harrad, 2015). However, an increasing number of studies have emphasized the importance of dietary intake as an exposure pathway Fromme et al, 2009;Harada and Koizumi, 2009;Vestergren et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…PFOS is globally distributed, persistent, bioaccumulative and potentially harmful to organisms, and so is of extensive concern. PFOS was categorized as a persistent organic pollutant (POP) in 2009 (Miralles-Marco and Harrad 2015).…”
mentioning
confidence: 99%